2020
DOI: 10.5194/isprs-archives-xliii-b2-2020-969-2020
|View full text |Cite
|
Sign up to set email alerts
|

3d Modelling in Temperate Waters: Building Rigs and Data Science to Support Glass Sponge Monitoring Efforts in Coastal British Columbia

Abstract: Abstract. Structure-from-motion (SfM) has emerged as a popular method of characterizing marine benthos in tropical marine environments and could be of tremendous value to glass sponge monitoring and management efforts in the Northeast Pacific Ocean. However, temperate marine environments present a unique set of challenges to SfM workflows, and the combined impact that cold, dark, and turbid waters have on the veracity of SfM derived data must be critically evaluated in order for SfM to become a meaningful tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 33 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…As dive time, and thus data collection, is constrained by depth, identifying the quantity and configuration of photographs required to maximise SfM performance was critical. While underwater SfM workflows have proven to be a relatively low-cost, simple, and informative method of documenting the 3D structure of benthic organisms in tropical regions, this wet-lab study, as well as prior dry-lab research (Lochhead and Hedley, 2021), were necessary steps preceding subsequent field surveys (Lochhead and Hedley, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As dive time, and thus data collection, is constrained by depth, identifying the quantity and configuration of photographs required to maximise SfM performance was critical. While underwater SfM workflows have proven to be a relatively low-cost, simple, and informative method of documenting the 3D structure of benthic organisms in tropical regions, this wet-lab study, as well as prior dry-lab research (Lochhead and Hedley, 2021), were necessary steps preceding subsequent field surveys (Lochhead and Hedley, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was found to be prudent that a clear set of data quality benchmarks is established before collecting field-based data: assessing the performance of HEXYZ-1 in a marine setting, quantifying the performance of the SfM workflow in cold, dark temperate waters, and identifying the relationship between the number of photograph, camera formation and 3D model accuracy. These distinct wet-lab tests provided an essential basis to inform field-based surveys (Lochhead and Hedley, 2020) and enabling informed decisions regarding the balance between data requirements, data quality and survey efficiency. This study confirmed that HEXYZ-1 is well equipped to provide camera stability and world-stabilised artificial light in a temperate marine environment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations